Structural and biophysical studies on sil silver resistance locus proteins SilP, SilR, and SilS - Casas-Mao, David E. (2018)
Upon the emergence of silver resistance in Salmonella enterica serovar Typhimurium, conferred by multi-resistance plasmid pMG101, it has become clear that a better understanding of the mechanisms of silver ion sensing, transport, and resistance would be of biomedical significance for the control of bacterial infection. This thesis describes protocols for cloning, overexpression, and purification of three of the nine bacterial proteins that are part of the sil resistance operon: a dedicated metal efflux pump (SilP), and a two-component regulatory system (SilR / SilS) that functions as a stimulus-response coupling mechanism triggered by high Ag(I) concentrations. SilP, SilR, and SilS have been prepared in amounts sufficient to undertake their study by Small Angle X-ray Scattering, Analytical Ultracentrifugation, Isothermal Titration Calorimetry, Circular Dichroism, Cryo-Electron Microscopy, and X-Ray diffraction. In addition, the SilP N-terminal Heavy Metal Binding Domain (HMBD) and a truncated SilP-HMBD construct were produced. Conditions leading to crystals of full-length SilP diffracting to 4.6 Å resolution, and of the HMBD at 1.5 Å resolution, as well as SilR microcrystals have been identified. SilP has been incorporated into styrene/maleic acid lipid particles to mimic its native membrane environment. SAXS analysis reveals that it adopts an elongated, flexible shape that exhibits only a modest reduction in axial ratio upon HMBD truncation. SilP-HMBD bound to AMP-PCP, a non-hydrolysable ATP analog, shows a compactly folded, monodisperse, highly structured conformation that is the best candidate for SilP crystals of improved size and quality. The apo-HMBD is a monomer with > 70% ordered structure (mostly α-helix). The HMBD becomes dimeric upon Ag(I) binding, and its -helical content is drastically reduced and transformed into -sheet. Two enthalpically-driven metal binding events, each involving 3 Ag+, occur sequentially with binding affinities (Kd) of 3 M and 15 M. Indeed, we report the crystal structure of the Ag(I)-HMBD, in which 3 Ag+ and a dozen ordered water molecules are shown in contact with 2 copies of its first metal binding site in the unit cell. The HMBD structure described herein is only the second example of a trinuclear monovalent ion cluster in the Protein Data Bank. We recognise its tridimensional structure in several metalloproteins with modest primary sequence homology, strongly suggesting that it constitutes a conserved structural fold. AUC and SAXS results show that unphosphorylated SilR is dimeric above 10 M, although it is expected to be predominantly monomeric intracellularly (from its predicted sub-M in vivo concentration and ca. 1 M KD dimerisation constant). SilR has similar levels of -helix (35%), - structure (34%), and random coil (31%), and forms a symmetric, elongated head-to-tail dimer. SilS, produced using bivariate induction of its recombinant expression, formed both dimers and monomers, depending on its concentration. SilS exhibits a compactly folded, elongated structure dominated by -structure and random coil that is assumed to be functional, as it was able to bind SilR only in the presence of Ag(I); neither SilS nor SilR was phosphorylated in our work. Finally, SilP and SilS sequences have been successfully embedded in SMALP nanodiscs, a significant advance towards the acquisition of a high-resolution structure by single-particle cryo- EM using this novel membrane protein scaffold.